Pengaruh User Interface, Perceived Security dan Perceived Privacy terhadap E-satisfaction Menggunakan Aplikasi Traveloka - Tamaro; Arif Sugiono; Diang Adistya; Jeni Wulandari (Journal of Technopreneurship on Economics and Business Review, 2021)
This research aims to analyse the effect of user interface, pereived security and perceived privacy on esatisfaction of traveloka users. The research uses an explanative approach. The sample of this study was Traveloka users aged 17 years and over with experience using the Traveloka. By using accidental sampling technique, the number of respondents is 385 people. Data analysis performed using descriptive analysis and multiple linear analysis. The results showed that the user interface, perceived security and perceived privacy partialy and simultaneously had a positive and significant effect on esatisfaction. The main e-satisfaction factor for traveloka users is user interface. The simpler and easier the user interface, increasing esatisfaction in using Traveloka